N-linked glycosylation enhances hemagglutinin stability in avian H5N6 influenza virus to promote adaptation in mammals. Issue 3 (8th June 2022) - Sun, Honglei; Deng, Guojing; Sun, Haoran; Song, Jingwei; Zhang, Wei; Li, Han; Wei, Xiaohui; Li, Fangtao; Zhang, Xin; Liu, Jiyu; Pu, Juan; Sun, Yipeng; et al.
Abstract: Clade 2.3.4.4 avian H5Ny viruses, namely H5N2, H5N6, and H5N8, have exhibited unprecedented intercontinental spread in poultry. Among them, only H5N6 viruses are frequently reported to infect mammals and cause serious human infections. In this study, the genetic and biological characteristics of surface hemagglutinin (HA) from clade 2.3.4.4 H5Ny avian influenza viruses (AIVs) were examined for adaptation in mammalian infection. Phylogenetic analysis identified an amino acid (AA) deletion at position 131 of HA as a distinctive feature of H5N6 virus isolated from human patients. This single AA deletion was found to enhance H5N6 virus replication and pathogenicity in vitro and in mammalian hosts (mice and ferrets) through HA protein acid and thermal stabilization that resulted in reduced pH threshold from pH 5.7 to 5.5 for viral-endosomal membrane fusion. Mass spectrometry and crystal structure revealed that the AA deletion in HA at position 131 introduced an N-linked glycosylation site at 129, which increases compactness between HA monomers, thus stabilizes the trimeric structure. Our findings provide a molecular understanding of how HA protein stabilization promotes cross-species avian H5N6 virus infection to mammalian hosts.